2021
DOI: 10.31557/apjcp.2021.22.1.145
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Factors Increasing the Risk of Radiation Toxicity in Patients with Early Breast Cancer

Abstract: Breast cancer is the second most commonly diagnosed cancer (11.6%) in both sexes after lung, among females, breast cancer is the most commonly diagnosed cancer, and it is the leading cause of cancer death (Bray et al., 2018). Radiotherapy has major advantages in the treatment of breast cancer. It reduces the risk of locoregional recurrences and improves overall survival both for early-stage breast cancer after breast-conserving surgery and after mastectomy for locally advanced disease (Darby et al., 2011). Unf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 30 publications
4
4
0
Order By: Relevance
“…The current study aimed to help define the prevalence of grade ≥2 ARD and RP in breast cancer patients treated with adjuvant RT. In our study, the prevalence of grade ≥2 ARD was 25.3%, which was well in the range of 3-76% reported in the literature (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24). In those studies that state the prevalence of grade ≥2 ARD irrespective of the type of fractionation, ARD rates ranged between 17% and 63% (11,(20)(21)(22)(23)26).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The current study aimed to help define the prevalence of grade ≥2 ARD and RP in breast cancer patients treated with adjuvant RT. In our study, the prevalence of grade ≥2 ARD was 25.3%, which was well in the range of 3-76% reported in the literature (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24). In those studies that state the prevalence of grade ≥2 ARD irrespective of the type of fractionation, ARD rates ranged between 17% and 63% (11,(20)(21)(22)(23)26).…”
Section: Discussionsupporting
confidence: 85%
“…ARD is the most common toxicity occurring during the course of RT or shortly afterwards (5). In previous studies, the prevalence of grade ≥2 ARD ranged between 3% and 76% (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26). Considering this wide range, additional studies are needed.…”
Section: Discussionmentioning
confidence: 99%
“…Second, PTR features show heterogeneity in the sample. However, Regarding the heterogeneity as reported in the fraction schedule [ 57 ], chemotherapy [ 65 ], surgery type [ 18 ], plan boost [ 46 ], treatment area [ 66 ], and nodal irradiation [ 67 ] in similar studies, it appears that these features have a heterogeneous nature. Therefore, considering potential variations in a homogeneous sample size, we recommend a cautious interpretation of the results.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, previous studies reported that elevated concentrations of serum biomarkers, including cancer antigen 15-3, carcinoembryonic antigen and cancer antigen 125, are associated with DM [ 34 , 59 ]. Future statistical and ML models could potentially guide routine CTC and serum biomarkers for specified high-risk groups and enable earlier detection of DM [ 60 , 61 ].…”
Section: Discussionmentioning
confidence: 99%